IMBALANCE BETWEEN E-NOS AND MRP4 GENE EXPRESSION IN TYPE 2 DIABETES MELLITUS MAY EXPLAIN THE HIGHER RISK OF NSTEMI IN DIABETIC SUBJECTS - Biasucci, Luigi M.; Rosa, Giulio La; Mandolini, Claudia; Grimaldi, Maria Chiara; Crea, Filippo (Journal of the American College of Cardiology, 2017)
Methods: MRP4 and eNOS mRNA expression were analyzed by RealTime PCR in platelets of 15 NSTEMI patients with (8) and without (7) T2DM compared to 20 patients with T2DM but without history of ischemic heart disease as control group.